Genetics - Taylor, Robert 1948- (Lucent library of science and technology, 2004)
Discusses the history and current state of scientific understanding of genetics, exploring the roles of genes, DNA, and RNA, as well as the medical, legal, and ethical dimensions of such issues as genetic engineering and DNA evidence.